SINTESIS MATERIAL BESI BERPENDUKUNG ZnAl2O4 (Fe/ZnAl2O4) DAN KARAKTERISASINYA - Eka Angasa; Sal Prima Yudha; Evi Maryanti; Taupik Rahman (Jurnal Riset Kimia, 2011)
ABSTRACT The aims of this work was to synthesize ZnAl2O4-supported iron material (Fe/ZnAl2O4). The Fe/ZnAl2O4 materials were prepared by impregnation of iron ions (FeCl3 and (NH4)2Fe(SO4)2 precursors) in solution to ZnAl2O4. Characterization of products using XRD shows that difractogram of Fe/ZnAl2O4 formed was similar to difractogram of Fe/ZnAl2O4 standard. This mean that ZnAl2O4-supported iron material has been successfully synthesized. Keywords: Iron, ZnAl2O4, impregnation